THE INFLUENCE OF MOTIVATION AND COMPETENCE OF HUMAN RESOURCES ON THE PERFORMANCE OF NURSES AT MURNI ASIH TANGERANG HOSPITAL - Rosa, Selvia; Mikrad (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This study aims to examine the influence of motivation and competence of human resources (HR) on the performance of nurses at Murni Asih Tangerang Hospital. This study used a quantitative method involving 93 respondents who were nurses in Murni Asih Tangerang Hospital using SPSS software version 27. Data analysis was carried out using multiple linear regression. The results of the study partially show that Motivation has a positive and significant influence on nurse performance. The results of the HR Competence research have a positive and significant influence on nurse performance. At the same time, the motivation and competence of human resources together have a significant effect on nurse performance. These results show that increasing motivation and developing human resource competence is an important factor in improving the performance of nurses in hospitals.